Environmental problems of organic pollutants: Hexabromocyclododecane - S.M. Akhmedov, Ph.D (Genius Journals, 2024)
This article investigates the environmental impact and toxicity of an organic pollutant called "hexabromocyclododecane" (GBSD). GBSD has been widely used as a flame retardant since the 1960s and is mainly found in building materials and other industrial products. This substance spreads over long distances due to its stability in the atmosphere, water and soil, which increases the environmental risk. The article also assesses the harmful effects of GBSD on human health and aquatic organisms, accumulation and stability over a long period of time. However, the article provides information on alternative products that replace GBSD, but emphasizes that they are not as effective as GBSD. The main conclusion of the article is that GBSD has a hazardous effect on the environment and has the nature of biological accumulation, so control is necessary to ensure environmental safety
Keywords: Hexabromocyclododecane; Organic Pollutant